Glass preform for optical fiber, and method for producing glass preform for optical fiber
Patent Information
- Application Number
- CN202210646147.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-01
- Filing Date
- 2022-06-09
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-06-09
AI Technical Summary
[0010]根据本发明,由于起始棒嵌入而一体接合于虚设玻璃的一端,所以即便在将虚设玻璃垂下而施加有荷重的状态下加热,也不易产生接缝附近的分离。
Smart Images

Figure CN115557691B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a glass matrix for optical fibers and a method for manufacturing the glass matrix for optical fibers. Background Technology
[0002] As a method for manufacturing glass matrix for optical fibers, there are known methods for sintering porous glass matrix obtained by VAD (vapor phase axial deposition) and OVD (outside vapor deposition).
[0003] Patent Document 1 describes a method in which glass microparticles for coating are deposited on the outer periphery of a starting component of a dummy glass that is fused to both ends of a starting rod, at the joint between the starting rod and the dummy glass, and on the outer periphery of a portion of the dummy glass. The deposited porous glass is then heated in a high-temperature furnace to form a transparent coating glass for making a glass matrix for optical fibers.
[0004] Regarding the method of connecting the starting rod and the dummy glass, Patent Document 2 describes a method in which the connecting part is smoothed by pressing a trowel against the connecting part and making the trowel "reciprocate". Patent Document 3 describes a method in which the outer diameter of the nodule portion is made to match the outer diameter of the dummy glass by repeatedly pressing and pulling the dummy glass and the starting rod together while heating the connecting part. [Existing Technical Documents] [Patent Literature]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-189428 [Patent Document 2] Japanese Patent Application Publication No. 6-199533 [Patent Document 3] Japanese Patent Application Publication No. 2014-80299 Summary of the Invention [The problem the invention aims to solve]
[0006] However, if the glass matrix for optical fibers manufactured using the method described above is then attached to a suspension shaft or similar hanging element in a later step, the dummy glass 1 is then... Figure 1A If heating is performed under a load, separation is likely to occur near the joint. Figure 1B The separation may cause damage to the glass matrix used in the optical fiber, so this is a problem. Figure 1C ).
[0007] For the starting rod, germanium is sometimes doped into the core to increase its refractive index. Additionally, fluorine is appropriately doped into the cladding layer to form recesses or grooves that lower the refractive index. In particular, when fluorine is doped into the portion of the starting rod that is joined to the dummy rod, separation is likely to occur near the joint.
[0008] Therefore, the present invention was made in view of the aforementioned situation, and its object is to suppress the separation of the starting rod from the dummy glass. [Technical means to solve the problem]
[0009] To address the aforementioned problem, the optical fiber glass matrix of the present invention is characterized by comprising: a starting rod; a dummy glass, embedded and integrally joined to one end of the starting rod; and a covering glass, surrounding a portion of the dummy glass and the starting rod. [The effects of the invention]
[0010] According to the present invention, since the starting rod is embedded and integrally joined to one end of the dummy glass, even when the dummy glass is heated under a load while hanging down, separation near the seam is not likely to occur. Attached Figure Description
[0011] Figure 1A This is a schematic diagram illustrating an example of the connection between a conventional starting rod and a dummy glass, as well as an example of the glass matrix used for optical fibers. Figure 1B This is a schematic diagram illustrating an example of the connection between a conventional starting rod and a dummy glass, as well as an example of the glass matrix used for optical fibers. Figure 1C This is a schematic diagram illustrating an example of the connection between a conventional starting rod and a dummy glass, as well as an example of the glass matrix used for optical fibers. Figure 2A This is a schematic diagram illustrating an example of the connection between the starting rod and the dummy glass of the present invention, and an example of the glass matrix for optical fibers. Figure 2B This is a schematic diagram illustrating an example of the connection between the starting rod and the dummy glass of the present invention, and an example of the glass matrix for optical fibers. Figure 2C This is a schematic diagram illustrating an example of the connection between the starting rod and the dummy glass of the present invention, and an example of the glass matrix for optical fibers. Figure 2D This is a schematic diagram illustrating an example of the connection between the starting rod and the dummy glass of the present invention, and an example of the glass matrix for optical fibers. Figure 2E This is a schematic diagram illustrating an example of the connection between the starting rod and the dummy glass of the present invention, and an example of the glass matrix for optical fibers. Detailed Implementation
[0012] Hereinafter, an example of a method for manufacturing the optical fiber glass matrix of the present invention will be described based on the accompanying drawings. Furthermore, the present invention is not limited to the embodiments described below.
[0013] In this embodiment, the glass matrix for optical fiber is formed by joining the dummy glass 1 with the starting rod 2. Figures 2A to 2D ), and form a covered glass 4 by surrounding a portion of the dummy glass 1 and the starting rod 2. Figure 2E It was made from ).
[0014] In the optical fiber glass matrix of the present invention, at the joint 3 between the dummy glass 1 and the starting rod 2, the dummy glass 1 is embedded and integrally joined to the starting rod 2. That is, the dummy glass 1 is joined with a portion extending deeper into the starting rod 2 than the end face of the starting rod 2. In subsequent steps, the optical fiber glass matrix is suspended by supporting the dummy glass 1 joined in this way, thus preventing separation near the joint 3.
[0015] Alternatively, the connection with the dummy glass 1 can be implemented at both ends of the starting rod 2. In this case, it has the following advantages: even if the dummy glass 1 is suspended by supporting either end, separation near the joint is not likely to occur.
[0016] The dummy glass 1 and the starting rod 2 are preferably airtightly joined at the joint 3. If an air bubble remains and is sealed in the joint 3, the starting rod 2 may sometimes separate from the dummy glass 1, starting from that air bubble.
[0017] The starting rod 2 is a component that forms the central part of the glass matrix used to manufacture the optical fiber. Preferably, it is doped with a dopant in a manner corresponding to the refractive index distribution of the target optical fiber. For example, it can be a hollow cylindrical rod, meaning the center is germanium (Ge)-doped silica glass, surrounded by pure silica glass or fluorine (F)-doped silica glass. (The starting rod can also be a hollow cylindrical rod.)
[0018] The shape of the joint 3 formed by the insertion end of the dummy glass 1 into the insertion end of the starting rod 2 is not particularly limited, but it is preferable that the dummy glass 1 and the starting rod 2 are joined with their central axes aligned. In this case, the stress distribution along the circumferential direction of the cross-section in the joint 3 becomes uniform. When the dummy glass 1 is a solid round rod, it is preferable that the central portion of the insertion end of the dummy glass 1 is inserted into the insertion end of the starting rod 2. Figure 2D It is particularly well-suited for situations where the outer diameter of the starting rod and the dummy glass are the same.
[0019] However, when using dummy glass containing more dopant impurities, there are cases where the viscosity of the dummy glass is lower than that of the starting rod when heated to the same temperature. In this case, the seam can also be processed by embedding the central portion of the starting rod's joint end into the joint end of the dummy glass. By processing in this way, the same effect as in this embodiment can be obtained.
[0020] In addition, like Figures 2A-2E Similarly, when the outer diameter of the dummy glass 1 is smaller than the outer diameter of the starting rod 2, it is preferable to form a state in which the joint end of the dummy glass 1 is entirely embedded in the joint end of the starting rod. On the other hand, when the outer diameter of the dummy glass is larger than the outer diameter of the starting rod, it is also possible to form a state in which the joint end of the starting rod is entirely embedded in the joint end of the dummy glass. The dummy glass can also be a cylindrical tube (hollow cylindrical rod), in which case the weight of the dummy glass becomes lighter.
[0021] This invention is particularly effective when the dummy glass 1, the starting rod 2, and the coating glass 4 contain different compositions of dopants. In this case, the seam 3 of the connecting part can be observed visually.
[0022] For example, the starting rod used in optical fibers is made of synthetic quartz glass with dopants such as germanium (Ge) and fluorine (F) added to adjust the refractive index. In contrast, the cladding glass is synthetic quartz glass that contains almost no of these dopants. These synthetic quartz glasses remove OH groups to reduce light absorption by keeping the OH group content below 1 ppm, and contain more than 100 ppm of chlorine (Cl). On the other hand, inexpensive natural quartz glass is often used as a dummy glass.
[0023] If the fiber is formed by combining three different types of glass—a dummy glass, an initiating rod, and a cladding glass—stress tends to concentrate near the joint. In later steps, the application of heat to this joint, and consequently, the application of almost the entire load on the fiber optic glass matrix, can easily lead to joint separation. The fiber optic glass matrix of this invention effectively suppresses the separation of such joints between different glass types, especially when the initiating rod is doped with fluorine. In this case, the effect is noticeable when the fluorine doping level is 0.7% by weight or less, and even more so when it is 0.5% by weight or less.
[0024] In the manufacturing method of the optical fiber glass matrix of the present invention, after the ends of the dummy glass 1 and the starting rod 2 are brought together by a processing device such as a glass lathe, ( Figure 2A After being softened by heating with a flame (not shown), it is pressed and fused together, and a coarse-diameter section 7 with an outer diameter larger than the dummy glass 1 or the starting rod 2 is made at the joint. Figure 2B ). When the machining trowel 8 is brought into contact with the rough diameter section 7 to level it, the bulge in the rough diameter section 7 is leveled by bringing the machining trowel 8 into contact with the rough diameter section and applying a load from the starting rod 2 side toward the dummy glass 1 side while moving it. Figure 2C ), forming a joint 3 by embedding the joint end of the dummy glass 1 into the joint end of the starting rod 2. Figure 2DHere, the term "leveling" the bulge of the rough diameter portion 7 refers to aligning it in a way that minimizes the difference between the outer diameter of the rough diameter portion 7 and the outer diameter of the starting rod 2. Preferably, the difference is 10% or less of the outer diameter of the starting rod 2, more preferably 5% or less. If the rough diameter portion 7 is not leveled, the flow of glass microparticles blown onto the starting rod 2 in the subsequent glass microparticle deposition step will be impaired, easily causing disorder in the formation of the glass microparticle deposition layer.
[0025] By employing this method, the rough diameter portion 7 can be easily shaped to complete the processing of the dummy glass 1 and the starting rod 2. This is achieved by embedding the end of the dummy glass 1 into the starting rod 2 (…). Figure 2D This design minimizes the risk of localized stress and load concentration, thus reducing the likelihood of glass separation. Furthermore, the seam 3 at the connection point, shown by the dashed line in the figure, is visually observable.
[0026] The embedding depth of the dummy glass into the starting rod can be adjusted, for example, by the diameter of the rough section formed by fusing the softened dummy glass with the end face of the starting rod. If the rough section is large, the embedding depth is processed to be larger; if the rough section is small, the embedding depth is processed to be smaller. Alternatively, it can be adjusted by changing the degree of softening of the glass by adjusting the heating temperature during the forming of the rough section, or by adjusting the load applied by the trowel and the trowel's movement speed during the forming of the rough section.
[0027] Furthermore, in this invention, it is preferable that at least one of the end faces of the starting rod and the dummy glass is convex before welding. When both end faces of the starting rod and the dummy glass are flat, air bubbles sometimes remain during welding of the end faces, and these air bubbles are trapped in the seam. By making at least one of the end faces convex, and welding while deforming the convex portion, a seam is formed, thus preventing air bubbles from remaining. Additionally, when shaping the rough diameter portion created during welding using a machining trowel, the rough diameter portion formed by connecting the convex portions to each other or by connecting the convex portions to a flat surface is smoother than the rough diameter portion formed by connecting the flat surfaces to each other, thus also having the advantage of being easier to shape.
[0028] For machining the convex front end, it is preferable to pre-grind it using a grinding machine or the like. The protrusion of the convex part can be either a central bulge or a convex part that is skewed outward from the center.
[0029] The protrusion amount is preferably between 0.5 and 2 times the radius. If the protrusion amount is less than 0.5 times, air bubbles are likely to remain; if it exceeds 2 times, the protrusion is likely to deform and sag during the heating process with a flame.
[0030] Furthermore, in this invention, the outer diameter of the dummy glass is preferably smaller than that of the starting rod. The main purpose of the dummy glass is to support the starting rod during the glass microparticle deposition and sintering steps, so it is not necessary to make the dummy glass excessively thick. In addition, as described above, by applying a load towards the dummy glass side to the thicker diameter portion (the portion where the outer diameter becomes thicker) formed at the joint between the starting rod and the dummy glass, the thicker diameter portion can be leveled, and the joint end of the dummy glass can be easily embedded into the joint end of the starting rod. (Although the size of the starting rod is determined by the size and refractive index distribution of the target optical fiber glass matrix,) when the dummy glass is as thin as possible, the heat, time, and load used for heating and bonding are reduced, making it easier to process. [Example]
[0031] A starting rod with a core, 50 mm in outer diameter and 1500 mm in length, made of synthetic quartz glass, with flat ends, is prepared for fabrication using the VAD process. This starting rod will distinguish the start and end sides of the VAD process. Furthermore, the starting rod prepared here is undoped with fluorine.
[0032] Using a glass lathe, one chuck holds the end face of the starting bar (manufacturing start side) towards another chuck, while the other chuck holds a dummy glass piece made of natural quartz glass with an outer diameter of 50 mm and a length of 500 mm. While rotating the chuck, the end face of the starting bar and the end face of the dummy glass are heated to approximately 2000°C using an oxyhydrogen flame from a burner until softened. This state is designated as (α).
[0033] [Example 1] For (α), the joint bulges (forming a rough diameter section) by bringing the clamps close together to fuse the end faces together. The maximum diameter of the bulging joint (rough diameter section) is 54 mm. While continuing to heat the joint using an oxyhydrogen flame, a high-purity carbon trowel is used to apply load and move along the starting rod side of the bulging joint (rough diameter section) towards the dummy glass side, thereby leveling the bulging joint (rough diameter section). The maximum diameter of the joint after the operation is 51 mm. At the joint, the dummy glass is embedded 1 mm into the starting rod.
[0034] [Example 2] For (α), the joint bulges (forming a rough diameter section) by bringing the clamps close together to fuse the end faces together. The maximum diameter of the bulging joint (rough diameter section) is 56 mm. While continuing to heat the joint using an oxyhydrogen flame, a high-purity carbon trowel is used to apply load and move along the starting rod side of the bulging joint (rough diameter section) towards the dummy glass side, thereby leveling the bulging joint (rough diameter section). The maximum diameter of the joint after the operation is 52 mm. At the joint, the dummy glass is embedded 3 mm into the starting rod.
[0035] [Example 3] For (α), the joint bulges (forming a rough diameter section) by bringing the clamps close together to fuse the end faces together. The maximum diameter of the bulging joint (rough diameter section) is 57 mm. While continuing to heat the joint using an oxyhydrogen flame, a high-purity carbon trowel is used to apply load and move along the starting rod side of the bulging joint (rough diameter section) towards the dummy glass side, thereby leveling the bulging joint (rough diameter section). The maximum diameter of the joint after the operation is 52 mm. At the joint, the dummy glass is embedded 5 mm into the starting rod.
[0036] For the connection between the starting rod and the dummy glass in Examples 1, 2, and 3, the dummy glass is held in place by a clamp. The clamp is then released from its hold on the starting rod. On the released side of the clamp, another dummy glass piece with an outer diameter of 50 mm and a length of 500 mm, made of natural quartz glass, is held in place. While rotating the clamp, each end face is heated to approximately 2000°C using an oxyhydrogen flame from a burner to soften it. The clamps are then brought close together, thereby fusing the dummy glass and the end face of the starting rod (manufacturing end side using the VAD method) together to form a bulging, large-diameter portion of the connection. The maximum diameter of the bulging connection (large-diameter portion) is 54 mm. By continuing to heat the connection (large-diameter portion) using an oxyhydrogen flame, a trowel is used to smooth the bulging (large-diameter portion) of the connection by moving back and forth between the starting rod side and the dummy glass side of the joint while the trowel is pressed against the bulging connection (large-diameter portion). Thus, a target material with dummy glass at both ends of the starting rod is formed.
[0037] The dummy glass at both ends of the target material formed through Examples 1, 2, and 3 is held in place by clamps at both ends of the chamber. Glass microparticles are deposited on the outer periphery of the target material using the OVD method, thereby producing a porous glass matrix with an outer diameter of 300 mm. The dummy glass of this porous glass matrix, attached to the starting side of the VAD manufacturing process on the starting rod, is connected to the front end of the shaft of the lifting mechanism of the dehydration sintering apparatus. The porous glass matrix is inserted into the furnace core tube of the dehydration sintering apparatus with the starting side of the VAD manufacturing process facing upwards and suspended vertically. While being heated at 1500°C, it is moved downwards to sinter the porous glass to make it transparent and vitrified, thereby producing a glass matrix for optical fibers.
[0038] In the configurations of Examples 1, 2, and 3, 10 optical fiber glass substrates were manufactured in each example. A load of 50 kgf was applied downwards while the dummy glass at the VAD manufacturing start side was held in place and suspended vertically. The seam between the starting rod and the dummy glass at the VAD manufacturing start side was visually observed, and the separation rate was investigated. Table 1 shows the results.
[0039] [Table 1]
[0040] In Examples 1, 2, and 3, a high separation suppression effect of less than 30% was confirmed. A comparison of Examples 1, 2, and 3 shows a tendency for a greater separation suppression effect with deeper embedding depth. In Example 1, the embedding depth of the dummy glass into the starting rod was 1 mm, which is equivalent to 2% of the outer diameter of the starting rod (50 mm). Therefore, it is believed that an embedding depth of 2% or more of the outer diameter of the starting rod results in a particularly excellent effect.
[0041] [Examples 4-7] As part of another study, a starting rod with an outer diameter of 50 mm and a length of 1500 mm, consisting of a core, made of synthetic quartz glass, was prepared and manufactured using the VAD method. For this starting rod, in order to form a recess on the outer periphery of the core, it was doped with fluorine in five different concentrations: 0 wt% (…Example 1), 0.1 wt% (…Example 4), 0.3 wt% (…Example 5), 0.5 wt% (…Example 6), and 0.7 wt% (…Example 7). The fluorine concentration of the starting rod was determined by melting a portion of the glass sheet obtained from pulverizing the starting rod and analyzing it using ion chromatography. Ten optical fiber preforms were manufactured from each of these starting rods in the same order as in Example 1.
[0042] [Compare Examples 1 and 2] In addition, a starting rod with an outer diameter of 50 mm and a length of 1500 mm, made of synthetic quartz glass and containing a core, was prepared to be manufactured using the VAD method. For this starting rod, in order to form a concave shape on the outer periphery of the core, it was doped with fluorine in two amounts: 0.5 wt% (...Comparative Example 1) and 0.7 wt% (...Comparative Example 2), thereby aiming to reduce the transmission loss of the optical fiber obtained by drawing the wire. The fluorine concentration of the starting rod was obtained by melting a portion of the glass sheet obtained from crushing the starting rod and analyzing it using ion chromatography.
[0043] For the starting bars in Comparative Examples 1 and 2, the end face of the starting bar, which is the manufacturing start side using the VAD method, is held by one chuck of a glass lathe facing towards another chuck. A dummy glass piece made of natural quartz glass with an outer diameter of 50 mm and a length of 500 mm is held by the other chuck. While rotating the chucks, the manufacturing start side end face of the starting bar and the end face of the dummy glass are heated to approximately 2000°C using an oxyhydrogen flame from a burner to soften them. By bringing the chucks close together, the end faces are fused together, causing the joint to bulge (forming a rough diameter section). The maximum diameter of the bulging joint (rough diameter section) is 54 mm. Then, while continuing to heat using an oxyhydrogen flame, a machining trowel is used to smooth the bulge of the joint by moving back and forth between the starting bar side and the dummy glass side of the seam while the bulge of the joint is pressed against the bulging joint (rough diameter section). The maximum diameter of the joint after the operation is 53 mm. However, unlike Examples 1-7, the joint between the dummy glass and the joint of the starting rod is joined in a planar manner.
[0044] For the connection between the starting rod and the dummy glass in Comparative Examples 1 and 2, while the dummy glass is held in place by a clamp, the clamp is released from its hold on the starting rod. On the released side of the clamp, another dummy glass piece, 50 mm in outer diameter and 500 mm in length, made of natural quartz glass, is held in place. While rotating the clamp, each end face is heated to approximately 2000°C using an oxyhydrogen flame from a burner to soften it. The clamps are then brought close together, thereby fusing the dummy glass and the end face of the starting rod (manufacturing end side using the VAD method) together to form a bulging, large-diameter section at the connection. The maximum diameter of the bulging connection (large-diameter section) is 54 mm. While continuing to heat the connection (large-diameter section) using an oxyhydrogen flame, a machining trowel is used to press against the bulging connection (large-diameter section) and move back and forth between the starting rod side and the dummy glass side of the joint, thereby smoothing the bulging (large-diameter section) of the connection. Thus, a target material with dummy glass at both ends of the starting rod is formed.
[0045] The dummy glass at both ends of the target material formed by Comparative Examples 1 and 2 is held in place by clamps at both ends of the chamber. Glass microparticles are deposited on the outer periphery of the target material using the OVD method, thereby producing a porous glass matrix with an outer diameter of 300 mm. The dummy glass of this porous glass matrix, which is attached to the starting side of the VAD manufacturing process of the starting rod, is connected to the front end of the shaft of the lifting mechanism of the dehydration sintering apparatus. The porous glass matrix is inserted into the furnace core tube of the dehydration sintering apparatus with the starting side of the VAD manufacturing process of the starting rod facing upwards and suspended vertically. While being heated at 1500°C, it is moved downwards to sinter the porous glass to make it transparent and vitrified. In this way, 10 glass matrixes for optical fibers are produced.
[0046] For the glass matrix used in the optical fiber, the seam between the starting rod and the dummy glass on the manufacturing start side was visually observed, and the separation rate was investigated. Table 2 shows the results.
[0047] [Table 2]
[0048] Based on the comparison between Example 5 and Comparative Example 1, and Example 7 and Comparative Example 2, it can be confirmed that even with the same fluorine doping concentration in the starting rod, by making the embedding depth / outer diameter of the starting rod 2% or more, seam separation can be significantly suppressed. The effects of the present invention can be confirmed when the fluorine doping amount in the starting rod is 0.7 wt% or less. Particularly high effects can be confirmed when the fluorine doping concentration in the starting rod is 0.5 wt% or less.
[0049] [Example 8] As part of another study, a starting rod with an outer diameter of 50 mm and a length of 1500 mm, made of synthetic quartz glass and containing a core, was prepared to be manufactured using the VAD method. The front end of the starting rod on the manufacturing start side was ground into a convex conical shape with a height of 30 mm using a disc grinder.
[0050] [Example 9] In addition, the two ends of a starting rod with an outer diameter of 50 mm and a length of 1800 mm, made of synthetic quartz glass and containing a core, manufactured using the VAD method, are held in place by chucks on both sides of a glass lathe. While the rod is softened by heating with an oxyhydrogen flame at a position 300 mm from the manufacturing start side, one of the chucks is moved and melted off, thereby shaping the front end of the manufacturing start side of the 1500 mm long starting rod into a convex parabolic cone with a height of 30 mm.
[0051] For the starting rods of Examples 8 and 9, 10 optical fiber glass preforms were manufactured in the same order as in Example 1. The seam between the starting rod and the dummy glass on the manufacturing start side was visually observed, and the separation rate was investigated. Table 3 shows the results.
[0052] [Table 3] End face shape of the starting rod flat cone Parabolic cone Seam separation rate 30% 0% 0%
[0053] In Examples 8 and 9, the seam separation rate was 0%. It is assumed that the convex shape at the front end prevents air bubbles from entering the seam, thus affecting the disappearance of the separation initiation point. While the end face shape of the starting rod was changed in Examples 8 and 9, the same effect could be achieved even by changing the end face shape of the dummy glass.
[0054] [Example 10] As part of another study, a starting rod with an outer diameter of 50 mm and a length of 1500 mm, made of synthetic quartz glass and containing a core, is prepared to be manufactured using the VAD method. Using a glass lathe, one chuck holds the starting face of the manufacturing start side of the starting rod towards another chuck, while the other chuck holds a dummy glass piece made of natural quartz glass with an outer diameter of 40 mm and a length of 500 mm. While rotating the chucks, the starting face of the starting rod and the end face of the dummy glass are heated to approximately 2000°C using an oxyhydrogen flame from a burner until softened. The chucks are then brought close together to fuse the end faces, creating a bulge at the joint. The maximum diameter of the bulge is 48 mm. While continuing to heat the joint using the oxyhydrogen flame, a high-purity carbon trowel is used to flatten the bulge by pressing it against the dummy glass side of the bulge. The maximum diameter of the joint after this process is 45 mm.
[0055] [Example 11] Using a glass lathe, one chuck holds the starting face of the manufacturing start side of the starting rod towards another chuck, while the other chuck holds a dummy glass piece made of natural quartz glass with an outer diameter of 60 mm and a length of 500 mm. While rotating the chucks, the starting face of the starting rod and the end face of the dummy glass are heated to approximately 2000°C using an oxyhydrogen flame from a burner to soften them. The chucks are then brought close together to fuse the end faces, creating a bulge at the joint. The maximum diameter of the bulge is 59 mm. While continuing to heat the joint using the oxyhydrogen flame, a high-purity carbon trowel is brought into contact with the bulge from the starting rod side towards the dummy glass side, thus smoothing the bulge. The maximum diameter of the joint after this process is 54 mm.
[0056] For the joints of the starting rod and the dummy glass in Examples 10 and 11, 10 optical fiber glass preforms were manufactured in the same order as in Example 1. The joint between the starting rod and the dummy glass on the manufacturing start side was visually observed, and the separation rate was investigated. Table 4 shows the results.
[0057] [Table 4] Outer diameter of the starting rod (mm) 50 50 50 The outer diameter (mm) of the fictitious glass. 50 40 60 Seam separation rate 30% 0% 10%
[0058] In Example 10, where the outer diameter of the starting rod is larger than the outer diameter of the dummy glass, the seam separation rate is 0%. Considering the cost of the dummy glass, it is preferable that the outer diameter of the starting rod is larger than the outer diameter of the dummy glass.
[0059] Furthermore, the present invention is not limited to the described embodiments and can be freely modified and improved as appropriate. [Explanation of Symbols]
[0060] 1. Fake glass 2. Starting rod 3. Seams 4. Covered glass 5. Separation 6. Damage to the glass matrix used in optical fibers 7. Rough diameter section 8. Machining trowels
Claims
1. A glass matrix for optical fibers, comprising: Starting bar; A dummy glass element is embedded and integrally joined to one end of the starting rod; as well as The glass is covered, surrounding a portion of the dummy glass and the starting rod; The dummy glass includes an embedded portion embedded inside the starting rod and an extension segment extending outward from the starting rod; at the boundary position with the embedded portion, the outer diameter of the extension segment is smaller than the outer diameter of the embedded portion.
2. The optical fiber glass matrix according to claim 1, wherein the starting rod is hermetically bonded to the dummy glass.
3. The optical fiber glass matrix according to claim 1 or 2, wherein the central portion of the junction end of the dummy glass is embedded in the junction end of the starting rod.
4. The optical fiber glass matrix according to claim 1 or 2, wherein the junction end of the dummy glass is embedded in such a way that it is enclosed by the junction end of the starting rod.
5. The glass matrix for optical fibers according to claim 1 or 2, wherein the starting rod contains germanium.
6. The glass matrix for optical fibers according to claim 1 or 2, wherein the starting rod contains fluorine.
7. The glass matrix for optical fibers according to claim 6, wherein the fluorine content is less than 0.7% by weight.
8. The glass matrix for optical fibers according to claim 6, wherein the fluorine content is less than 0.5% by weight.
9. The optical fiber glass matrix according to claim 1 or 2, wherein the outer diameter of the dummy glass is less than or equal to the outer diameter of the starting rod.
10. The optical fiber glass matrix according to claim 1 or 2, wherein the embedding depth of the dummy glass into the starting rod is more than 2% of the outer diameter of the starting rod.
11. The optical fiber glass substrate according to claim 1 or 2, wherein the dummy glass is a solid rod or a hollow cylinder.
12. The glass matrix for optical fibers according to claim 1 or 2, wherein the starting rod is a solid rod.
13. A method for manufacturing a glass matrix for optical fibers, comprising the following steps: Heat and join one end of the starting rod to the other end of the dummy glass. A coarse diameter portion with an outer diameter larger than that of the dummy glass and the starting rod is formed at the joint between the starting rod and the dummy glass. The trowel is brought against the rough diameter section, and while a load is applied from the starting rod side of the rough diameter section toward the dummy glass side, the trowel is moved to form a joint where the joint end of the dummy glass is embedded into the joint end of the starting rod. A glass microparticle layer is deposited on the outer periphery of the dummy glass and the starting rod; and The glass microparticle layer is heated to make it transparent.
14. The method for manufacturing a glass matrix for optical fibers according to claim 13, wherein the starting rod is doped with fluorine.
15. The method for manufacturing a glass matrix for optical fibers according to claim 13 or 14, wherein the starting rod is doped with fluorine at a rate of 0.7% by weight or less.
16. The method for manufacturing a glass matrix for optical fibers according to claim 13 or 14, wherein the starting rod is doped with fluorine at a rate of 0.5% by weight or less.
17. The method for manufacturing a glass matrix for optical fibers according to claim 13 or 14, further comprising the step of processing at least one end of the starting rod or one end of the dummy glass into a convex shape.
18. The method for manufacturing a glass matrix for optical fibers according to claim 13 or 14, wherein the outer diameter of the dummy glass is less than or equal to the outer diameter of the starting rod.
Citation Information
Patent Citations
Method for working optical fiber preform
JP1994199533A
Production of optical fiber preform
JP1999189428A
Manufacturing method of optical fiber preform connected with dummy rod and manufacturing method of dummy rod
JP2014080299A
Method for preparing optical fiber by large-sized low-water-peak optical fiber preform and dedicated device therefor
CN1884165A
Quartz-based optical fiber
JP1986063543A